Editorial - Aguirre Chavez, Felipe (2024)
Following the proverb: “If you want to go fast, go alone. If you want to go far, go accompanied.” Since its founding, Educa UMCH magazine has opted for collaborative work between national and international researchers as a means of permanent learning for innovation, creativity and the development of capabilities that make it possible to find new ways of doing things and solving problems.